Total organic carbon and total nitrogen measured on MUC samples during Island Pride cruise IP21 (MANGAN21) to the BGR and GSR license areas in the Clarion Clipperton Fracture Zone - Lara Macheriotou; Bruno Vlaeminck; Nene Lefaible; Bart Beuselinck; Ann Vanreusel; Jolien Goossens (PANGAEA, 2022)
This dataset contains sedimentary parameters total nitrogen (TN) and total organic carbon (TOC) measured from Multicorer (MUC) samples from the Bundesanstalt für Geowissenschaften und Rohstoffe (BGR, Germany) and Global Sea Mineral Resources (GSR, Belgium) license areas in the Clarion Clipperton Fracture Zone (CCFZ) collected on onboard the Norwegian Island Pride during expeditions Mangan21 in 2021. Total organic carbon (TOC) and total nitrogen (TN) was quantified by combustion of freeze-dried samples with the Flash 2000 NC Sediment Analyser. These data were collected to quantify nutrients in the CCFZ and to correlate these values to observed levels of biodiversity. Values are given in their respective units (SI) and have been collected and measured by the Marine Biology Research Group of Ghent University (Belgium).